Strategi Pemasaran Efektif untuk Meningkatkan Produksi dan Pendapatan Usaha Jamur Tiram (Studi Kasus PT Timur Mushroom Farm Desa Kuajang Kecamatan Binuang Kabupaten Polewali Mandar Sulawesi Barat) - Niken Ayu Mardianti; Saadah Saadah; Rahmawaty A Nadja; A. Nixia Tenriawaru; Ni Made Viantika Sulianderi (Department of Agribusiness, Halu Oleo University Jointly with Perhimpunan Ekonomi Pertanian Indonesia - Indonesian Society of Agricultural Economics (PERHEPI/ISAE), 2024)
Mushrooms are a horticultural plant with many benefits for the human body and are easily cultivated and processed into products. However, many people do not know how to process oyster mushrooms, especially in the Polewali Mandar area, so PT Timur Mushroom Farm was established as a company that develops oyster mushroom cultivation. The research aims to describe internal and external factors and formulate alternative strategies more effective for companies in increasing production and income. The study was conducted in 2023 by combining two methods or a mixture of qualitative and quantitative methods. The data source is primary data obtained through interviews with the owner of PT Timur Mushroom Farm, while the variables in the study are marketing strategy and marketing mix. Secondary data is obtained indirectly through intermediary media such as journal theses from parallel research. Informants in the study ranged from 3 people with data analysis methods in the form of IFE and EFE matrices to determine the company's internal and external factors. The SWOT matrix brings up new strategies that can help the company develop, and the QSPM matrix determines which alternative strategies are prioritized to increase production and company revenue. The results showed 17 internal and external factors in the company. Alternative strat.